2001
DOI: 10.1074/jbc.m010077200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Distinct Cholesterol Domains in Fiber Cell Membranes from Cataractous Human Lenses

Abstract: Previous studies in our laboratory have provided direct evidence for the existence of distinct cholesterol domains within the plasma membranes of human ocular lens fiber cells. The fiber cell plasma membrane is unique in that it contains unusually high concentrations of cholesterol, with cholesterol to phospholipid (C/P) mole ratios ranging from 1 to 4. Since membrane cholesterol content is disturbed in the development of cataracts, it was hypothesized that perturbation of cholesterol domain structure occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 58 publications
(50 reference statements)
3
64
0
Order By: Relevance
“…Direct analysis of membranes isolated from early-stage cataractous lenses revealed that cholesterol domains were more pronounced and more stable than those of normal lens membranes. This was true despite a significantly lower (ϳ54%) C/P mole ratio (82). It was speculated that these structural changes may be due to modification of the lens membrane by age-related insults, such as lipid peroxidation.…”
Section: Discussionmentioning
confidence: 79%
“…Direct analysis of membranes isolated from early-stage cataractous lenses revealed that cholesterol domains were more pronounced and more stable than those of normal lens membranes. This was true despite a significantly lower (ϳ54%) C/P mole ratio (82). It was speculated that these structural changes may be due to modification of the lens membrane by age-related insults, such as lipid peroxidation.…”
Section: Discussionmentioning
confidence: 79%
“…2 and 12 ). Phospholipid oxidation promotes cholesterol-domain formation ( 198 ), and these domains are distinct from those formed with nonoxidized membranes ( 199 ). The relative amount of cholesterol is lowest in the outer cortical region of the lens where the molar cholesterol-phospholipid ratio is 1:2 ( 197,200,201 ).…”
Section: Cataract Lens Lipids Lifespan and Mortalitymentioning
confidence: 99%
“…Evidence for immiscible cholesterol-rich and -poor domains in normal lens fiber cell membrane was reported, 14 and cholesterol-rich domains were more pronounced and better defined in cataractous lens. 15 Previously, lipid raft domains were isolated and lipids 13 and caveolin-1 16 content was examined. Sorting of AQP0 and connexins to raft and nonraft domains was also reported.…”
mentioning
confidence: 99%